2020
DOI: 10.4143/crt.2019.145
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin C Interacts with TNF-α/p38 MAPK Signaling Pathway to Promote Proliferation and Metastasis in Hepatocellular Carcinoma

Abstract: Although cathepsin C (CTSC) has been reported to maintain malignant biological properties in various cancers, its functions in hepatocellular carcinoma (HCC) remain obscure. We aimed to investigate the potential role of CTSC in HCC. Materials and Methods HCC tissue microarrays (n=122) were employed to analyze the correlation between CTSC expression and clinicopathological characteristics through immunohistochemistry staining. Quantitative real-time polymerase chain reaction, western blot assay, Cell Counting K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 30 publications
1
39
0
Order By: Relevance
“…The target genes of the miRNAs were enriched in Ras signaling pathway, PI3K-Akt signaling pathway, MAPK signaling pathway and so on, which might be potential mechanisms of HCC vascular invasion. There were studies displayed that activated Ras signaling could promote HCC proliferation [38], and MAPK signaling pathway was associated with epithelial-tomesenchymal transition, invasion, and metastasis in HCC [39,40]. Additionally, activation of the PI3K/AKT pathway could also promote HCC progression [41].…”
Section: Discussionmentioning
confidence: 99%
“…The target genes of the miRNAs were enriched in Ras signaling pathway, PI3K-Akt signaling pathway, MAPK signaling pathway and so on, which might be potential mechanisms of HCC vascular invasion. There were studies displayed that activated Ras signaling could promote HCC proliferation [38], and MAPK signaling pathway was associated with epithelial-tomesenchymal transition, invasion, and metastasis in HCC [39,40]. Additionally, activation of the PI3K/AKT pathway could also promote HCC progression [41].…”
Section: Discussionmentioning
confidence: 99%
“…In the tumor development and metastasis, p38 MAPK signaling pathway is activated as a frequent event (28,29). p38 MAPK pathway was dysregulated in HCC tissues compared with the corresponding normal tissues (30). Increasing number of studies have demonstrated that miRNAs interacted with signaling pathways in a variety of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…By attaching to TNF-α R-1 and TNF-α R-2 [ 26 ], the cytokine impacts tumor development via multiple mechanisms, such as contributing to EMT, boosting the cell proliferation rate and accelerating angiogenesis, among others [ 40 , 41 , 42 ]. The aberrant expression of TNF-α was found in a variety of neoplastic diseases, including prostate cancer, ovarian cancer, liver cancer and breast cancer [ 43 , 44 , 45 , 46 ]. The antitumor activities of TNF-α have been leveraged in cancer treatments [ 47 ].…”
Section: Inflammation and Cancermentioning
confidence: 99%